Does Xaje Nasir-oddin-e Tusi Believe in Three-valued Logic? - Ali Reza Darabi; Asad _allahe falahiy (Metaphysics, 2009)
In his book Asaso Al-eqtebas, Xaje Nasir-od-dine-e Tousi has given an analysis of connected conditional propositions which is similar to the analysis of the conditional propositions in three-valued logic. It raises the following question: does Tusi accept propositions with values other that “True” and “False”? In this article we consider Tusi’s view and those of his followers, and compare it with those who accept the three valued logic. We will show that Xaje didn’t believe that propositions can have a third value. Also we will show that in his analysis of connected conditional proposition Xaje Nasir does not use the word “true” and “false” as they are commonly used by other logicians. They are rather used to mean true and false in the analytic sense. We conclude, therefore, that in the text we consider “true” and “false” are not used in their ordinary and common sense. They are used, rather, homonymsly.